EFFECTIVENESS OF USING ANIMATED VIDEO MEDIA IN IMPROVING KNOWLEDGE OF MAINTENANCE OF DENTAL AND ORAL HYGIENE (Study Students of VII & VIII grade of SMPN Diponegoro Surabaya in 2024): EFEKTIVITAS MENGGUNAKAN MEDIA VIDEO ANIMASI DALAM MENINGKATKAN PENGETAHUAN PEMELIHARAAN KEBERSIHAN GIGI DAN MULUT (Studi Pada Siswa kelas VII & VIII SMPN Diponegoro Surabaya Tahun 2024) - Aini Rahmawidya; Silvia Prasetyowati; Ratih Larasati (Poltekkes Kemenkes Surabaya, 2024)
The student learning process to get a success to change behavior in the learning process requires a means to convey good and interesting material. Videos are very attractive to generation 4.0 who are closer and like more sophisticated use, especially videos have funny and unique characters Dental and oral hygiene is a healthy condition that includes the ability to speak, smell, taste, chew, swallow, and express various facial expressions with confidence. Research Problem Based on the initial data of dental examination in appendix 3 on September 25, 2023 with a total of 47 students in classes VII and VIII of SMPN Diponegoro Surabaya, the debris index value was 2.0 or 82.9% of students were in the bad category because the SMPN only conducted UKS activities once a year and only checked for cavities. The purpose of the study was to find out the effectiveness of using video media. animation in increasing knowledge of maintaining dental and oral hygiene in classes VII and VIII of SMPN Diponegoro Surabaya. This type of research uses a pre-experimental design with one group pretest-posttest. The targets of this study were VII & VIII grade students of Diponegoro Junior High School Surabaya with 47 respondents. Data collection methods using questionnaire sheets. The results of the study of animated video media can effectively increase students' knowledge of dental and oral hygiene.